Pilot study on the use of basophil activation tests and skin tests for the prevention of allergic transfusion reactions - Akiki, Philippe; Dedeken, Laurence; Ferster, Alina; Doyen, Virginie; Dupire, Gwendy; Nagant, Carole; Smet, Julie; Ghorra, Nathalie; Ruth, Isabelle; Lauwers, Maïlis; Daubie, Valery; Corazza, Francis; et al. (Frontiers in Allergy, 2024)
Background and objectives Management of severe allergic transfusion reactions (ATR) is challenging. In this study, we investigate the usefulness of skin tests and basophil activation tests (BAT) in chronically transfused patients for the prevention of future ATR. Materials and methods BAT and skin tests were carried with the supernatant of red blood cell (RBC) units for a sickle-cell disease patient under chronic exchange transfusion who has presented a severe ATR, in order to prevent potential future ATR. If the results for both BAT and skin tests were negative, the RBC units could be transfused to the patient. If either one of the results was positive, the tested RBC unit was discarded for the patient. Results 192 RBC units were tested with both tests. The level of results concordance between the two tests was 95%. Out of the 169 negative units with both tests, 118 units were transfused to the patient for which he presented no ATR. Conclusion In our study, combining both BAT and skin tests was associated with a good negative predictive value since we were able to safely transfuse our patient. Further studies are still necessary to confirm this result but this pilot study indicates that skin tests and BAT might help prevent ATR. When BAT is not available, skin tests may also be useful in preventing ATR.